2002
DOI: 10.1038/labinvest.3780450
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel Morphology and Vascular Endothelial Growth Factor Expression in Human Colonic Carcinoma With or Without Metastasis

Abstract: SUMMARY:We quantified microvessel morphology and vascular endothelial growth factor (VEGF) expression in human colonic carcinoma with or without metastasis. The cancerous growth and the noncancerous section of surgical specimens from 36 patients with colorectal carcinoma (14 without metastasis and 22 with metastasis) were studied. Tissue slices immunostained with CD34 were processed for microvessel counts (per mm 2 ), the mean diameter of microvessels ( m), and the mean spatial direction of microvessels (degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…It has been reported that CD34 is expressed both in blood vessels and lymphatics, but blood vessels stain more intensely. 24,25,36 Thus, the total number of vessels we counted may be an underestimation of the true value. However, this did not bias our findings, as evident from sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that CD34 is expressed both in blood vessels and lymphatics, but blood vessels stain more intensely. 24,25,36 Thus, the total number of vessels we counted may be an underestimation of the true value. However, this did not bias our findings, as evident from sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We counted the total number of vessels (both blood and lymphatic) using the pan-endothelial marker CD34. 24,25 A monoclonal antibody raised against podoplanin, as described previously 26,27 (kindly provided by Dr Geleff, Department of Pathology, University of Vienna, Austria), and the commercial monoclonal antibody D2-40 (SIG-730, Signet Laboratories, Dedham, MA, USA, dilution 1:40) were used to stain lymphatic vessels in two adjacent sections. Immunohistochemistry was performed using the EnVision System (DAKO, Copenhagen, Denmark), as previously described.…”
Section: Tissue Samplesmentioning
confidence: 99%
“…VEGF peptide (VEGF [A-20]: sc-152 P; Santa Cruz Biotechnology) was used for VEGF neutralization. As positive human control tissues, tonsil, rheumatoid arthritis synovium, and colon tumor were used (30)(31)(32).…”
Section: Expression Of Vegf In Polymyositis and Dermatomyositismentioning
confidence: 99%
“…These differences in results have been attributed in part to limitations in the traditional method for assessing angiogenesis 7,8,23 . Among other factors involved, it can be mentioned that, with the conventional method, only the number of microvessels is evaluated, while other information like the size of the vessels, for example, is disconsidered 11 . This forms the justification for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional way of quantifying angiogenesis consists of the counting of microvessels on a histological thin section. Lately computerized analysis of histological images have allowed the measurement of vascular parameters, and several studies have also reported a relationship between prognosis and angiogenesis expression 9,10,11 . The aim of the current study was to examine the relationship between angiogenesis and prognosis of colorectal cancer either by manual counting of microvessels density or by computer-assisted analysis of endothelial area.…”
Section: Introductionmentioning
confidence: 99%